Studi Pemanfaatan Limbah Penambangan Granit pada Karakteristik Kekuatan Tanah Laterit untuk Konstruksi Timbunan Jalan - Irwan, Andesta Granitio; Arif, Maulana; Bayu, Hendi Hendra; Aditiawan, Riski; Panita, Shakila (Civil Engineering Departement, Andalas University, 2024)
Local laterite soil in the Bangka Belitung Islands is one of the main materials in civil engineering construction, especially embankments. Several studies related to laterite soil suggest that laterite soil is often damaged by water and also causes reduced compaction. This study aims to identify the specifications and characteristics of laterite soil as embankment construction with the addition of granite dust waste as a mixture to stabilize the soil as an embankment. The study was conducted on a laboratory scale by testing the physical and mechanical properties of the original soil and granite dust mixture according to the mixture scheme of 0%, 5%, 10%, 15%, 25% and 30%. The results show that local laterite soil is included in the Silty Clay group with medium-low plasticity, the addition of granite dust changes the characteristics of the soil so that there is a decrease in the plasticity value which is specifically suitable for embankments. The addition of granite dust makes soil compaction easier with increased density and decreased water content, optimal compaction occurs in a mixture of 30% granite dust. The addition of granite dust increases the CBR value of the soil so that it enters the road embankment specification requirements, namely >6% for a mixture of 5-15% and optimally at 10%. Compressive strength testing shows that the increase in compressive strength after the addition of granite dust mixture where the 10% mixture is the condition of the soil having optimal strength under axial load.